Multiple component‐pharmacokinetic studies on 10 bioactive constituents of Peiyuan Tongnao capsule using parallel reaction monitoring mode. (13th May 2021) - Wang, Chenxi; Xing, Yanchao; Ding, Hui; Wang, Ping; Zhang, Lihua; Fu, Zhifei; Han, Lifeng; Pang, Xu
Abstract: Peiyuan Tongnao capsule (PTC) plays an important role in clinical application due to its excellent curative efficacy in the treatment of ischemic stroke and chronic cerebral circulation insufficiency. To standardize and rationalize the clinical application of PTC, a rapid and sensitive method based on ultra‐high performance liquid chromatography/quadrupole‐Orbitrap mass spectrometry with parallel reaction monitoring (PRM) mode was developed and validated for the pharmacokinetic (PK) study. Ten bioactive compounds (aucubin, salidroside, echinacoside, paeoniflorin, verbascoside, liquiritin, 2, 3, 5, 4′‐tetrahydroxy stilbene‐2‐ O ‐ β ‐d ‐glucoside, coumarin, glycyrrhizic acid, and emodin) were simultaneously determined in rat plasma. All calibration curves exhibited good linearity ( r 2 > 0.99). The lower limits of quantification were 0.082–13.291 ng mL −1 . The intra‐ and inter‐day precision was 0.54–12.36%, whereas the intra‐ and inter‐day accuracy ranged from 100.45 to 114.00%. The mean extraction recoveries were 81.77–117.66%, and the average matrix effects (MEs) were 86.23–109.96%. The high extraction recoveries and acceptable MEs indicated that the pretreatment method was feasible. And the stability was acceptable under various storage conditions and processing procedures. The validated method was successfully applied to the multiple components‐PK studies, which lay the foundation for further pharmacological and clinical research of PTC and may provide a reference for other traditional Chinese medicines.